2020
DOI: 10.3390/microorganisms8030324
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily-Related Helicobacter pylori Genotypes and Gastric Intraepithelial Neoplasia in a High-Risk Area of Northern Italy

Abstract: Helicobacter pylori (Hp) is the major recognized risk factor for non-cardia gastric cancer (GC), but only a fraction of infected subjects develop GC, thus GC risk might reflect other genetic/environmental cofactors and/or differences in virulence among infectious Hp strains. Focusing on a high GC risk area of Northern Italy (Cremona, Lombardy) and using archived paraffin-embedded biopsies, we investigated the associations between the Hp vacA and cagA genotype variants and gastric intraepithelial neoplasia (GIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…H. pylori strains are characterized by marked genetic heterogeneity, which may result in various clinical consequences of the persistence of these bacteria [ 16 ]. Most people infected with H. pylori have no clinical manifestations of infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori strains are characterized by marked genetic heterogeneity, which may result in various clinical consequences of the persistence of these bacteria [ 16 ]. Most people infected with H. pylori have no clinical manifestations of infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peculiarities of the genetic structure of an infectious agent may significantly affect the nature of changes in the mucosa of the upper gastrointestinal tract. As a result, they may affect the development, course, and prognosis of gastric diseases, as well as the effectiveness of therapy [ 14 , 15 , 16 ]. This demonstrates the importance of studying the genetic structure of H. pylori in helicobacter-associated diseases of the stomach and duodenum.…”
Section: Introductionmentioning
confidence: 99%
“…A 349-bp product indicated presence of cagA . To determine the variability in the EPIYA domains, the 3′ variable region was amplified using primers cag2 and cag4 resulting in products of 550-850-bp [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The PCR reaction mix consisted of 1.7 mM MgCl 2 , 0.2 mM dNTPs, 1 U of Platinum ® Taq DNA polymerase (Invitrogen, Carlsbad, CA, USA), and 300 ng of total DNA in a total volume of 25 μL.…”
Section: Methodsmentioning
confidence: 99%
“…31 Intraepithelial neoplasia requires a three or six-month period of close follow-up or ESD. 32 This study found that atrophy of the gastric mucosa caused by Hp infection could be divided into five stages as follows: glandular atrophy of the lamina propria, compensatory proliferative atrophy, intestinal metaplasia atrophy, smooth muscle proliferative atrophy, and proliferative zone atrophy. Accordingly, the histopathological characteristics of atrophy at each stage were studied along with the immunophenotypic characteristics.…”
mentioning
confidence: 90%